2021
DOI: 10.3390/toxins13050357
|View full text |Cite
|
Sign up to set email alerts
|

N58A Exerts Analgesic Effect on Trigeminal Neuralgia by Regulating the MAPK Pathway and Tetrodotoxin-Resistant Sodium Channel

Abstract: The primary studies have shown that scorpion analgesic peptide N58A has a significant effect on voltage-gated sodium channels (VGSCs) and plays an important role in neuropathic pain. The purpose of this study was to investigate the analgesic effect of N58A on trigeminal neuralgia (TN) and its possible mechanism. The results showed that N58A could significantly increase the threshold of mechanical pain and thermal pain and inhibit the spontaneous asymmetric scratching behavior of rats. Western blotting results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…To trace back to the phosphate groups from LRRK2 , LRRK2 pull-down and IP assays of trigeminal root entry zone of TN were conducted to detect a variety of enzymes that catalyze phosphate group transmission. We noticed that MAPK/ERK signaling pathway was the top affected item in TN ( Figure 3(c) ) and was reported to participate in pathogenesis neuralgia in previous studies [ 34 , 35 ]. We harvested ERK1/2 from the LRRK2 binding proteins ( Figure 6(c) ).…”
Section: Resultsmentioning
confidence: 75%
“…To trace back to the phosphate groups from LRRK2 , LRRK2 pull-down and IP assays of trigeminal root entry zone of TN were conducted to detect a variety of enzymes that catalyze phosphate group transmission. We noticed that MAPK/ERK signaling pathway was the top affected item in TN ( Figure 3(c) ) and was reported to participate in pathogenesis neuralgia in previous studies [ 34 , 35 ]. We harvested ERK1/2 from the LRRK2 binding proteins ( Figure 6(c) ).…”
Section: Resultsmentioning
confidence: 75%
“…It has been shown that MAPK activation in the spinal cord or primary afferent nerve promotes nociceptor hyperexcitability and induces changes in neuronal plasticity, which is associated with neuropathic and inflammatory pain (Yu et al., 2016 ). As reported, scorpion analgesic peptide N58A exerts significant analgesic effects on CCI‐ION rat models possibly by decreasing the phosphorylation levels of MAPK signaling protein (C. L. Li et al., 2021 ). Additionally, miR‐125a‐3p attenuates the maintenance of orofacial inflammatory pain through negatively regulating p38 MAPK in rat trigeminal ganglions (Y. Dong et al., 2014 ).…”
Section: Discussionmentioning
confidence: 78%
“…reported, scorpion analgesic peptide N58A exerts significant analgesic effects on CCI-ION rat models possibly by decreasing the phosphorylation levels of MAPK signaling protein (C. L Li et al, 2021)…”
mentioning
confidence: 99%
“…Many studies have highlighted the effect of disturbances in ion channels on neuropathic pain. This resembles the disturbances observed among NVC patients (Charlesworth et al, 2012;Wei et al, 2013;Choi et al, 2016;Li et al, 2021;Romero et al, 2021). Interestingly, the relationships between disturbances in ion channels and NVC have been explored in a few papers.…”
Section: Disturbances In Ion Channelsmentioning
confidence: 99%